Entre la republicanización y la militarización. Las transformaciones de las fuerzas policiales en la Segunda República española, 1931-1936 - Sergio Vaquero Martínez (Ler História, 2017)
This article analyses the democratisation of the police forces during the Spanish Second Republic, an incomplete process with advances and setbacks. In 1931 the Provisional Government purged the dictatorship´s more prominent policemen and created the Assault Guard, an anti-riot force equipped with batons, pistols, and motorised vehicles. Then the Republican-Socialist governments attempted to “republicanise” the state forces, increased the Assault Guard, subordinated the Civil Guard to the executive power, and transferred the police services of Catalonia to the Generalitat. However, after the conservative turn of the 1933 election, the Radical-Cedist cabinets rectified these measures: they militarised the police, handed back the control of the Civil Guard to the military, re-centralised the management of public order in Catalonia, and took a hard repressive stance against strikes and demonstrations. The Popular Front rulers recovered the reformist policies of the first biennium, although the increase of disorders and violent clashes, as well as the politicisation and loss of authority of the police, delegitimized these reforms, which were eventually interrupted on July 1936 by the failed coup d’État organised by the military that led to the Civil War.